Pengaruh Terpaan Kekerasan Media Audio-Visual Pada Kognisi Agresif dan Afeksi Agresif Studi Meta-Analisis - Mirra N Milla (Faculty of Psychology, Universitas Gadjah Mada, 2006)
This article provides a meta-analitic review of the effect of exposure to audio visual media violence on aggressive cognition and aggressive affect. Exposure to audio visual media violence significantly enhanced aggressive cognition and aggres¬sive affect when the findings aggregated across studies, but the effect was not uniform across investigations. Only suggestive evidence was obtained concerning mode¬rators of effect, media type, sex and social situation (laboratory vs natural setting). Keywords: meta-analysis, audio vidual media violence, aggressive cognition, aggressive affect